2017
DOI: 10.1016/j.jcps.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Just do it! Why committed consumers react negatively to assertive ads

Abstract: Research shows that assertive ads, which direct consumers to take specific actions (e.g., Visit us; Just do it!), are ineffective due to reactance. However, such ads remain prevalent. We reexamine assertive ads, showing that their effectiveness depends on consumers' relationship with the advertising brand. Across studies, we compare committed and uncommitted consumers' reactions to assertive ads. We find that because committed (vs. uncommitted) brand relationships involve stronger compliance norms, assertive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 69 publications
(162 reference statements)
4
56
1
2
Order By: Relevance
“…For those who do not think environmental issues are important, assertive language is perceived as more threatening, and in line with reactance theory, produces negative effects (Kronrod, Grinstein, & Wathieu, ). Similar effects were reported by Zemack‐Rugar, Moore, and Fitzsimons (), who found that assertive ads reduced compliance (e.g., purchase frequency) for those who were committed to a brand (i.e., had a strong consumer—brand connection), and this effect was serially mediated by anticipated guilt for ignoring the message and pressure to comply.…”
Section: Complex Languagesupporting
confidence: 80%
See 1 more Smart Citation
“…For those who do not think environmental issues are important, assertive language is perceived as more threatening, and in line with reactance theory, produces negative effects (Kronrod, Grinstein, & Wathieu, ). Similar effects were reported by Zemack‐Rugar, Moore, and Fitzsimons (), who found that assertive ads reduced compliance (e.g., purchase frequency) for those who were committed to a brand (i.e., had a strong consumer—brand connection), and this effect was serially mediated by anticipated guilt for ignoring the message and pressure to comply.…”
Section: Complex Languagesupporting
confidence: 80%
“…The use of the word “please” in “Please recycle” adds politeness to an assertive statement, and thus politeness can potentially serve to soften the perceived pushiness of a strongly assertive slogan or appeal. However, in the only research of which we are aware that tested this possibility, the addition of a politeness marker to an assertive ad appeal (“Buy now” vs. “Please buy now”) had no effect (Zemack‐Rugar et al., ).…”
Section: Complex Languagementioning
confidence: 94%
“…While previous research on reactance has shown how specific attributes of a message such as vividness of the message (Quick and Stephenson 2008), assertiveness of the language used in the message (Zemack-Rugar, Moore, and Fitzsimons 2017), and source of the message (Bushmann and Stack 1996) influence psychological reactance, little is known about how reactance may differ according to how different consumer groups view the source of the message. Our findings contribute to the reactance literature by showing how individual differences, in particular, political ideology, can influence the way an individual responds to the source of a perceived freedom-restricting message.…”
Section: Discussionmentioning
confidence: 99%
“…Reactance can result from a myriad of factors including product unavailability, manipulative advertising, government regulations, promotional influence (Clee and Wicklund 1980; Laurin, Kay, and Fitzsimons 2012; Miyazaki, Rodriguez, and Langenderfer 2009), unsolicited advice that contradicts initial impressions (Fitzsimons and Lehmann 2004), explicitness of the message (Burgoon et al 2002), spatial confinement (Levav and Zhu 2009), and forcefulness of the language used in the message (Quick and Stephenson 2008; Zemack-Rugar, Moore, and Fitzsimons 2017). For instance, when experts’ advice contradicts consumers’ initial impression of choice options, choice share of the option that is recommended by experts may go down due to reactance (Fitzsimons and Lehmann 2004).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Методы императивного воздействия на потребителей наиболее распространены на рынке (например, реклама, открыто продвигающая преимущества продуктов/услуг и призывающая потребителей их приобрести, или «холодные» звонки). Однако данный тип воздействия постепенно теряет свою эффективность по мере развития рынка и накопления потребителями ЗМВ [Zemack-Rugar, Moore, Fitzsimons, 2017]. Методы воздействия в рамках императивной стратегии имеют относительно низкую вероятность влияния на мнение критически настроенных и грамотных потребителей, но в отношении потребителей с низким уровнем маркетинговой грамотности и маркетингового скептицизма они могут быть эффективны.…”
Section: рис 3 типология потребителей по уровню маркетингового скепunclassified